MO554THE EFFECT OF HEMOGLOBIN CHANGES AND THE SEVERITY OF CHRONIC KIDNEY DISEASE IN PHYSICAL FUNCTION IN ELDERLY PATIENTS WITH HEART FAILURE. (29th May 2021) - Noda, Takumi; Kamiya, Kentaro; Hamazaki, Nobuaki; Nozaki, Kohei; Ichikawa, Takafumi; Yamashita, Masashi; Uchida, Shota; Yoshikoshi, Shun; Maekawa, Emi; Yamaoka-Tojo, Minako; Matsunaga, Atsuhiko; Ako, Junya
Abstract: Background and Aims: Anemia is frequently observed in patients with heart failure (HF) and causes increased hospitalization and mortality rates. Anemia is also associated with and is a major risk factor of impaired physical function and frailty. On the other hand, a high percentage of elderly patients with HF have chronic kidney disease (CKD), which is an aggravating factor for anemia, and the combination of anemia and CKD has been reported to increase physical dysfunction and mortality. However, the relationship between hemoglobin (Hb) changes and physical function during hospitalization in elderly patients with HF is unclear, and the impact of CKD severity on these relationships is also unclear. This study aimed to examine the relationship between Hb changes and physical function during hospitalization in elderly patients with HF. We further examined the relationship when stratified by CKD severity. Method: Seven hundred and thirty-seven elderly patients with HF, who underwent changes in Hb and physical function test (leg strength, gait speed, and 6-min walking distance [6MWD]), were included in this study. Using a multiple linear regression model, associations between Hb changes and physical function were assessed. In addition, using a generalized linear mixed model, we divided the HF patients into three groups with eGFR ≥60, 30–60, and <30, and examined whether the severity of CKD was related to the Hb change and physical function. Results: The median age of the subjects in this study was 77 years (interquartile range 72–82). Changes in Hb during hospitalization were independent determinants of physical function (leg strength, β: 0.158, P < 0.001; gait speed, β: 0.023, P < 0.001; 6MWD, β: 13.039, P < 0.001), even after accounting for factors related to severity of HF. Moreover, the group with more severe CKD showed significantly lower physical function, although Hb improved ( P < 0.001) with respect to leg strength and 6MWD compared with the group with lower CKD stage. Conclusion: Hb change during hospitalization was an independent determinant of physical function in patients with HF. Patients with a more severe CKD showed lower leg strength values and 6MWD even if Hb improved.